2019
DOI: 10.1136/bmjgh-2019-001644
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of chronic kidney disease in low-income and middle-income countries: development and validation of a point-of-care screening strategy for India

Abstract: IntroductionAlthough deaths due to chronic kidney disease (CKD) have doubled over the past two decades, few data exist to inform screening strategies for early detection of CKD in low-income and middle-income countries.MethodsUsing data from three population-based surveys in India, we developed a prediction model to identify a target population that could benefit from further CKD testing, after an initial screening implemented during home health visits. Using data from one urban survey (n=8698), we applied ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
(38 reference statements)
2
28
0
Order By: Relevance
“…16,17 In order to study CKD provoking factors, sample was divided into two groups; with and without CKD, hypertension prevalence was higher in those with CKD, in agreement with Bradshaw et al, Narenpitak et al, Hooi et al, and Jolly et al; DM and hypertension are independent risk factors and responsible for 15% of CKD. 4,30,[36][37][38][39] Heart disease prevalence was higher in those with CKD in agreement with Bradshaw et al and (Jolly et al; cardiovascular risk increase as eGFR drop, death related to heart disease was 2-3 times in those with stage 3 and 4 CKD, respectively, than that with normal kidney function. 4,21,36,38 Those with CKD are more likely to be unemployed with no income which is in agreement with Bradshaw et al Females' percent was higher in those with CKD which is in agreement with Hooi et al 37 ; as age-related diabetic kidney disease progression differ between sexes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…16,17 In order to study CKD provoking factors, sample was divided into two groups; with and without CKD, hypertension prevalence was higher in those with CKD, in agreement with Bradshaw et al, Narenpitak et al, Hooi et al, and Jolly et al; DM and hypertension are independent risk factors and responsible for 15% of CKD. 4,30,[36][37][38][39] Heart disease prevalence was higher in those with CKD in agreement with Bradshaw et al and (Jolly et al; cardiovascular risk increase as eGFR drop, death related to heart disease was 2-3 times in those with stage 3 and 4 CKD, respectively, than that with normal kidney function. 4,21,36,38 Those with CKD are more likely to be unemployed with no income which is in agreement with Bradshaw et al Females' percent was higher in those with CKD which is in agreement with Hooi et al 37 ; as age-related diabetic kidney disease progression differ between sexes.…”
Section: Discussionsupporting
confidence: 88%
“…4,30,[36][37][38][39] Heart disease prevalence was higher in those with CKD in agreement with Bradshaw et al and (Jolly et al; cardiovascular risk increase as eGFR drop, death related to heart disease was 2-3 times in those with stage 3 and 4 CKD, respectively, than that with normal kidney function. 4,21,36,38 Those with CKD are more likely to be unemployed with no income which is in agreement with Bradshaw et al Females' percent was higher in those with CKD which is in agreement with Hooi et al 37 ; as age-related diabetic kidney disease progression differ between sexes. 40 Those living in periphery are more likely to have CKD; in low income countries where unaffordable costly health service, unawareness, 41 unemployment and DM epidemic in Iraq, making CKD a leading cause of death and lately referred CKD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Chronic kidney disease (CKD) is a signi cant global health problem and one of the top 20 causes of death worldwide. It is a serious threat to people's life and health [20,21]. CKD DALYs is calculated by adding the YLLs and the YLDs, we found that the age-standardized YLL rate is much higher than the YLD rate at the global level and in various income regions, suggesting that premature death is the main cause of CKD burden.…”
Section: Resultsmentioning
confidence: 82%
“…[2][3][4]7,8,11,12 Publications available about POCT methods aimed at nephrologic patients are mostly for diagnosis and do not include BGA. [13][14][15][16] To the best of our knowledge, the present study assesses clinical, operative, and economic outcomes of POCT BGA in a nephrology department for the first time.…”
mentioning
confidence: 99%